2009
DOI: 10.1007/s10463-009-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Conditional likelihood estimation and efficiency comparisons in proportional odds model with missing covariates

Abstract: Missing value, Proportional odds model, Ordinal categorical data, Conditional likelihood,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Note that v 1 , …, v m denote the distinct values of V i . Hsieh et al (2010) proposed a Breslow and Cain (1988) type estimator of Θ based on the validation data set. The large‐sample theory was presented under the assumption that the observed covariates and surrogate variables are categorical.…”
Section: Review Of the Conditional Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that v 1 , …, v m denote the distinct values of V i . Hsieh et al (2010) proposed a Breslow and Cain (1988) type estimator of Θ based on the validation data set. The large‐sample theory was presented under the assumption that the observed covariates and surrogate variables are categorical.…”
Section: Review Of the Conditional Estimation Methodsmentioning
confidence: 99%
“…Based on (), the estimation score for Θ is expressed as follows: where The CEM estimator of Θ , denoted by , is the solution of . Hsieh et al (2010) compared the efficiencies of several estimators of the parameters based on different estimation approaches of in model (). They showed that the CEM estimators that use the nonparametric estimators for are more efficient than those based on the true selection probabilities.…”
Section: Review Of the Conditional Estimation Methodsmentioning
confidence: 99%